MENYOAL BUDAYA “BERELAAN” DALAM AKAD JUAL-BELI DI KALIMANTAN TENGAH MENURUT SYARI’AT ISLAM - Iman, Noor (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The purpose of this research is to analyze how the culture of mutual consent (berelaan) in sales and purchase agreements is viewed from the perspective of Islamic law, with the hope of encouraging the broader community (especially Muslims) to remain attentive to principles and guidelines that are considered appropriate both socially and religiously. This study uses library research as its methodology, incorporating a local wisdom approach, with findings presented descriptively. The results indicate that the culture of berelaan in sales transactions in Central Kalimantan holds strong moral and religious values when properly applied, as it emphasizes mutual agreement between seller and buyer. However, when values of sincerity and willingness begin to fade from the transaction process, it can affect the legal validity of the sales practices that have traditionally been upheld. Furthermore, the loss of the original intent or essence of sincerity in the berelaan culture can give rise to negative attitudes such as distrust, suspicion, and disharmony between the parties involved. Consequently, this deterioration can potentially disrupt the close social bonds that have long been fostered through buying and selling interactions, and in worse cases, may even damage the ties of silaturahmi (social harmony and kinship), which are essential to communal life in Central Kalimantan.